Glutamate ionotropic receptor NMDA type subunit 2A (GRIN2A) gene polymorphism (rs4998386) and Parkinson's disease susceptibility: A meta‐analysis - Nepal, Gaurav (Aging Med (Milton), 2019)
OBJECTIVE: Dopaminergic neuronal degeneration seen in Parkinson's disease (PD) might result from a single nucleotide polymorphism (SNP) in the glutamate ionotropic receptor NMDA type subunit 2A (GRIN2A) gene. We thus performed a meta‐analysis exploring the relationship between the rs4998386 SNP of the GRIN2A gene and PD susceptibility. METHODS: We searched PubMed, EMBASE, Web of Science, Google Scholar, and China National Knowledge Infrastructure for studies published between January 2005 and January 2019. The association between the rs4998386 polymorphism and PD susceptibility was evaluated by calculating the pooled odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS: Meta‐analysis results did not show a significant association between the rs4998386 polymorphism of the GRIN2A gene and PD susceptibility when assuming an allelic model (OR, 0.90; 95% CI, 0.76‐1.07; P = .22; I (2 )= 53%), a dominant model (OR, 0.96; 95% CI, 0.82‐1.12; P = .62; I (2 )= 64%), or a recessive model (OR, 1.14; 95% CI, 0.93‐1.38; P = .22; I (2 )= 0%). CONCLUSION: Our meta‐analysis found that the rs4998386 polymorphism of the GRIN2A gene is not associated with risk of PD in either Europeans or white Americans. However, large sample studies with different ethnicities should be conducted to establish the role of the rs4998386 polymorphism in PD pathophysiology.